PERSEPSI PENGUNJUNG TERHADAP WISATA ALAM DI CAMP GRANIT TAMAN NASIONAL BUKIT TIGAPULUH - Sinaga, Ave Nova; Yoza, Defri; Volcerina Darlis, Viny (Wahana Forestra: Jurnal Kehutanan, 2020)
Bukit Tiga Puluh National Park (TNBT) became a representative of lowland tropical rain forests on the island of Sumatra because it has high aesthetic value and an interesting diversity of flora and fauna, TNBT ecosystem has the potential to be developed as a natural tourist attraction. Camp Granit's nature tourism has interesting objects, both natural and artificial. The purpose of this research was to determine visitor perceptions and visitor's travel motives towards nature tourism at Camp Granit TNBT. The information were collected by field observations with an inventory of natural attractions, using a questionnaire technique. This research used quantitative descriptive methods. The results of this research showed that Camp Granit's nature tourism has a very attractive tourist environment, the level of comfort when traveling is classified as very comfortable and the level of tourist satisfaction is classified as very satisfied and on the travel motives of visitors to Camp Granit nature tourism TNBT with a recreational or vacation destination of 68.60%.